The role of personality and home office practices in developing organizational commitment: The post-COVID-19 Hungarian case - Anita Kozák; Ervin István Markó; Gabor Arva (Problems and Perspectives in Management)
Since organizational commitment has been shown to contribute to the success of an enterprise and is acknowledged to be influenced by both personality and situational factors, a thorough investigation into how home office arrangements shape the personality-commitment bonds is needed to provide HR practitioners with guidelines on how to establish effective home office policies. Therefore, this study seeks to investigate whether the relationships between the Big Five personality traits and the three facets of organizational dedication still exist in the post-COVID-19 era characterized by an ever-increasing adoption of remote working and, if so, to reveal whether remote working arrangements shape these relationships. Using data collected from 730 Hungarian employees working in various industries in late 2023 via a self-administered questionnaire and employing PLS-SEM analysis, the study confirms that personality-commitment relationships persist in the post-COVID-19 era. On the other hand, the associated effect sizes, which range from 0.008 to 0.053, also reveal that organizational commitment is primarily driven by factors other than personality, which explains less than 10% of the variability in organizational commitment. Moreover, the non-significant moderating effect of the home office suggests that remote working practices do not fundamentally shape the strength of the relationships between the personality and the dedication toward an organization. Consequently, different personality traits required for fulfilling specific roles do not need special attention when developing remote work policies; rather, openness and extraversion, the two primary sources of dedication, are to be prioritized to promote organizational commitment.